IMPLEMENTASI PENINGKATAN KUALITAS DAN EFISIENSI OPERASIONAL UMKM MELALUI PENDEKATAN QUALITY FUNCTION DEPLOYMENT (QFD) PADA PENGGILINGAN BAKSO DI KOTA BATAM - Brigida Endah Nuraeni; Edi Sumarya; Abdullah Merjani (Jurnal Pengabdian Bukit Pengharapan, 2025)
This community service program aims to improve service quality and operational efficiency of the Penggilingan Bakso Jawa Timur MSME in Batam City through the Quality Function Deployment (QFD) approach. The main problems identified include inconsistent grinding results, long service times, and high machine noise levels that reduce customer comfort. The implementation method adopts a participatory approach by integrating Voice of Customer (VOC), Critical to Quality (CTQ), and process improvement interventions, including the development of Standard Operating Procedures (SOP), machine maintenance, workspace layout rearrangement, and queue system implementation. Evaluation is conducted by comparing pre- and post-intervention conditions based on operational performance indicators. The results indicate significant improvements in grinding consistency (≥90%), a reduction in defective products by 75%, and a 40% decrease in service time. Additionally, there is a 25% increase in the number of customers and daily revenue. The implementation of quality control and quality assurance has proven effective in enhancing operational performance and customer satisfaction. Therefore, the integration of QFD with VOC and CTQ can serve as a strategic approach to improve competitiveness and sustainability of MSMEs in the food processing sector.